Machine Learning for credit risk in the Reactive Peru Program: a comparison of the Lasso and Ridge regression models - Geraldo Campos, Luis Alberto (2022)
COVID-19 has caused an economic crisis in the business world, leaving limitations in the continuity of the payment chain, with companies resorting to credit access. This study aimed to determine the optimal machine learning predictive model for the credit risk of companies under the Reactiva Peru Program because of COVID-19. A multivariate regression analysis was applied with four regressor variables (economic sector, granting entity, amount covered, and department) and one predictor (risk level), with a population of 501,298 companies benefiting from the program, under the CRISP-DM methodology oriented especially for data mining projects, with artificial intelligence techniques under the machine learning Lasso and Ridge regression models, with econometric algebraic mathematical verification to compare and validate the predictive models using SPSS, Jamovi, R Studio, and MATLAB software. The results revealed a better Lasso regression model (λ60 = 0.00038; RMSE = 0.3573685) that optimally predicted the level of risk compared to the Ridge regression model (λ100 = 0.00910; RMSE = 0.3573812) and the least squares model with algebraic mathematics, which corroborates that the Lasso regression model is the best predictive model to detect the level of credit risk of the Reactiva Peru Program. The best predictive model for detecting the level of corporate credit risk is the Lasso regression model. La COVID-19 ha provocado una crisis económica en el mundo empresarial, dejando limitaciones en la continuidad de la cadena de pagos, con empresas recurriendo al acceso al crédito. El objetivo de este estudio es determinar el modelo predictivo óptimo de aprendizaje automático para el riesgo crediticio de las empresas del Programa Reactiva Perú, como consecuencia de la COVID-19. Se aplicó un análisis de regresión multivariado con cuatro variables regresoras (sector económico, entidad otorgante, monto cubierto y departamento) y un predictor (nivel de riesgo), con una población de 501.298 empresas beneficiarias del programa, bajo la metodología CRISP-DM, orientada especialmente para proyectos de minería de datos, con técnicas de inteligencia artificial bajo los modelos de regresión de machine learning Lasso y Ridge y con verificación matemática algebraica econométrica para comparar y validar los modelos predictivos utilizando los software SPSS, Jamovi, R Studio y MATLAB. Los resultados revelaron un mejor modelo de regresión de Lasso (λ60 = 0,00038; RMSE = 0,3573685) el cual predijo de manera óptima el nivel de riesgo en comparación con el modelo de regresión de Ridge (λ100 = 0,00910; RMSE = 0,3573812) y el modelo de mínimos cuadrados con matemáticas algebraicas, lo que corrobora que el modelo de regresión de Lasso es el mejor modelo predictivo para detectar el nivel de riesgo crediticio del Programa Reactiva Perú. El mejor modelo predictivo para detectar el nivel de riesgo de crédito corporativo es el modelo de regresión de Lasso.